1976
DOI: 10.1113/jphysiol.1976.sp011229
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of uptake2 in the termination of activity of neurogenic noradrenaline in the rat isolated atrium.

Abstract: SUMMARY1. An examination has been made of the relative effect of drugs which affect Uptake, and Uptake2 on the mechanical responses to adrenergic nervous stimulation (0.5-5 Hz for 5 see) in rat isolated atrium.2. Inhibition of Uptake1 with desmethylimipramine (2 ,UM) prolonged by 50-90% the time taken for recovery of normal heart rate after a five see train of nervous stimulation. Inhibition of Uptake2 with metanephrine (4#M) prolonged by 20-40% the time taken for recovery of normal heart rate.3. Neither desme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1977
1977
1985
1985

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The relaxation of smooth muscles after exposure to excitatory neurotransmitters is widely accepted to be dependent on the rate of inactivation of these agents within the tissue (Kalsner & Nickerson, 1968;Draskoczy & Trendelenburg, 1970;Trendelenburg & Henseling, 1976), and upon this assumption the mechanisms responsible for the inactivation of noradrenaline after its release from nerve terminals have been investigated in vitro (Brandao & Guimaraes, 1974;Bell & Grabsch, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…The relaxation of smooth muscles after exposure to excitatory neurotransmitters is widely accepted to be dependent on the rate of inactivation of these agents within the tissue (Kalsner & Nickerson, 1968;Draskoczy & Trendelenburg, 1970;Trendelenburg & Henseling, 1976), and upon this assumption the mechanisms responsible for the inactivation of noradrenaline after its release from nerve terminals have been investigated in vitro (Brandao & Guimaraes, 1974;Bell & Grabsch, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…is consistent with our results. Similarly, Bell & Grabsch (1976) demonstrated that prolonged (> 25 s) chronotropic responses of rat heart to noradrenaline released in 5 s stimulus trains were prolonged by uptake inhibition.…”
Section: Ionophoretic Gaba Responsesmentioning
confidence: 99%
“…Chronotropic responses of isolated, paired atria to intramural adrenergic nerve stimulation were studied by the method reported in a previous paper (Bell & Grabsch, 1976). 5 sec trains of 0-5 msec monophasic square-wave pulses were delivered at frequencies of 1 and 5 Hz and supramaximal voltage.…”
Section: Isolated Atriamentioning
confidence: 99%
“…In view of the apparent absence of involvement of Uptake2 in terminating vascular responses to catecholamines we examined responses to adrenergic nerve stimulation of isolated atria, where Uptake2 has been shown previously to be concerned in termination of the response (Bell & Grabsch, 1976 DMI by Bell & Grabsch (1976) (Fig. 4) (Fig.…”
Section: Effect Of Uptake2 Inhibition On Responses To Adrenergic Nervmentioning
confidence: 99%